STRUCTURE OF RAILWAY LOCOMOTIVES IN CENTRAL ASIA - Lutfulloev S. F. (Ecomind Press, 2025)
This article examines the structure and operational features of railway locomotives with a focus on their technical complexity and relevance to the development of transport infrastructure in Uzbekistan. As rail transport continues to play a critical role in connecting regions and supporting economic growth, understanding the internal architecture and functioning of locomotives is essential for students and professionals in the railway industry. The paper discusses the key components of locomotives, including power systems, transmission, braking, and control units, and analyzes their significance in ensuring efficient and safe train movement. It also explores recent developments and modernization trends in locomotive design, particularly in response to energy efficiency demands and environmental regulations. Drawing on both local and international sources, the article aims to equip future specialists with a comprehensive understanding of locomotive mechanics and their application in real-world railway operations.
Keywords: Locomotive design, traction systems, railway engineering, energy efficiency, train operation, Uzbekistan rail transport, technical components.